Social goals of Filipino adolescents: Do they contribute to student life satisfaction? - Ouano, Jerome A. (Animo Repository, 2012)
Premised on positive psychology and the social rootedness of students’ motivation, the study explored the effects of social goals on student life satisfaction. Using a predictive cross-sectional non-experimental design, the five social goals from the formulation of Dowson and McInerney (2004) were tested as predictors of the five dimensions of Huebner’s (2001) student life satisfaction among 302 college students who responded to self-report questionnaires. Results provided evidence for the potential contribution of social goals on student life satisfaction. Social affiliation goal predicted student’s satisfaction with friends, school, living environment, and self, but not with family. Social responsibility goal predicted satisfaction with family, school, living environment, and self, but not with friends. Social status goal predicted satisfaction with family, friends, and self, but not with school and living environment. Social approval and social concern goals predicted all the dimension of student life satisfaction. Discussion centers on how the students’ endorsement of each social goal contributes to their life satisfaction.